2013
DOI: 10.3856/vol41-issue1-fulltext-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a commercial probiotic on bacterial and phytoplankton concentration in intensive shrimp farming (Litopenaeus vannamei) recirculation systems

Abstract: ABSTRACT. The aim of this study was to evaluate the effect of a commercial probiotic on the bacterial and phytoplankton concentration in intensive shrimp farming (Litopenaeus vannamei) with a recirculation system, for one culture period in Rio Grande do Norte, Brazil. Ponds, with mean area of 2.6 ha, were stocked with a density of 98 shrimp m -2 . A commercial probiotic was prepared following the manufacture's specifications and sprayed on the surface of the ponds seven days prior to stocking and then on a wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 41 publications
(41 reference statements)
1
20
2
1
Order By: Relevance
“…In some studies, microbial product supplementation resulted in the reduction of ammonia, nitrite, nitrate, total nitrogen and organic matter and the increase in survival and production of the farmed animals (Chen & Chen, ; Janeo, Corre & Sakata, ; Kuhn, Drahos, Marsh & Flick, ; Liang et al., ; Liu & Han, ; Nimrat, Suksawat, Boonthai & Vuthiphandchai, ; Shariff, Yusoff, Devaraja & Rao, ; Vovk, Bazaeva & Didenko, ; Wang & He, ; Wang, Xu & Xia, ; Wu et al., ; Zhang et al., , ; Zink, Benetti, Douillet, Margulies & Scholey, ; Zokaeifar et al., ). In the other studies, supplementation of microbial products did not significantly improve production performance and water quality of aquaculture practices (Boyd, Hollerman, Plumb & Saeed, ; Chiayvareesajja & Boyd, ; Li & Boyd, ,b; Lukwambe et al., ; McIntosh et al., ; de Paiva‐Maia, Alves‐Modesto, Otavio‐Brito, Olivera & Vasconcelos‐Gesteira, ; Queiroz & Boyd, ; Talpur, Ikhwanuddin, Abdullah & Bolong, ; Tang, Dai, Li, Qin & Wang, ; Zheng, Tang, Ren, & Wang, ; Zhou, Wang & Li, ). The environmental impacts of exogenous bacteria depend on survival of the bacteria in the new surrounding and their competitions with native bacteria (El Fantroussi & Agathos, ; Ninawe & Selvin, ; Skjermo, Bakke, Dahle & Vadstein, ).…”
Section: Introductionmentioning
confidence: 89%
“…In some studies, microbial product supplementation resulted in the reduction of ammonia, nitrite, nitrate, total nitrogen and organic matter and the increase in survival and production of the farmed animals (Chen & Chen, ; Janeo, Corre & Sakata, ; Kuhn, Drahos, Marsh & Flick, ; Liang et al., ; Liu & Han, ; Nimrat, Suksawat, Boonthai & Vuthiphandchai, ; Shariff, Yusoff, Devaraja & Rao, ; Vovk, Bazaeva & Didenko, ; Wang & He, ; Wang, Xu & Xia, ; Wu et al., ; Zhang et al., , ; Zink, Benetti, Douillet, Margulies & Scholey, ; Zokaeifar et al., ). In the other studies, supplementation of microbial products did not significantly improve production performance and water quality of aquaculture practices (Boyd, Hollerman, Plumb & Saeed, ; Chiayvareesajja & Boyd, ; Li & Boyd, ,b; Lukwambe et al., ; McIntosh et al., ; de Paiva‐Maia, Alves‐Modesto, Otavio‐Brito, Olivera & Vasconcelos‐Gesteira, ; Queiroz & Boyd, ; Talpur, Ikhwanuddin, Abdullah & Bolong, ; Tang, Dai, Li, Qin & Wang, ; Zheng, Tang, Ren, & Wang, ; Zhou, Wang & Li, ). The environmental impacts of exogenous bacteria depend on survival of the bacteria in the new surrounding and their competitions with native bacteria (El Fantroussi & Agathos, ; Ninawe & Selvin, ; Skjermo, Bakke, Dahle & Vadstein, ).…”
Section: Introductionmentioning
confidence: 89%
“…The PCA results revealed that application of B. subtilis FY99‐01 could increase the abundance of Bacillariophyta and Chlorophyta in the late phase of culture. Similarly, De Paiva‐Maia, Alves‐Modesto, Otavio‐Brito, Olivera and Vasconcelos‐Gesteira () have reported that using commercial probiotics composed of Bacillus spp., Lactobacillus spp. and yeasts change the percentage value of Pyrrophyta in shrimp culture water.…”
Section: Discussionmentioning
confidence: 89%
“…Researchers are inclined to think that it could be both factors; furthermore, it would be important to determine whether probiotics actually taste good to aquaculture species (Irianto and Austin, 2002a,b). The effects of probiotics were observed in phytoplankton (microalgae), which form the basis of aquatic food chains (Paiva-Maia et al, 2013) because of its nutrient-producing photosynthetic mechanisms; in most cases, higher organisms were unable to synthesize polyunsaturated fatty acids and vitamins (Bonnet et al, 2010;Tang and Suter, 2011). Gomez-Gil et al (2002) assessed the possibility of coculturing the shrimp probiotic C 7 b in the presence of the shrimp larvae food Chaetoceros muelleri, without affecting microalga, proposed that these organisms can be grown together to achieve a high density, and fed to shrimp.…”
Section: Source Of Nutrients and Enzymatic Contribution To Digestionmentioning
confidence: 99%
“…These probiotic bacteria regulate the microbiota of aquaculture water and control pathogenic microorganisms to enhance the decomposition of undesirable organic substances in the water and sediment because of the improved ecological environment of aquaculture (Xiang-Hong et al, 2003;Venkateswara, 2007). Paiva-Maia et al (2013) studied the effect of a commercial probiotic on the bacterial and phytoplankton concentrations in intensive shrimp farming of Litopenaeus vannamei with a recirculation system. The results indicated that probiotics caused marked change in the total heterotrophic bacteria count in the sediment and percentage values of Pyrrophyta concentrations, improving the environmental quality of the sediment and water in ponds with closed recirculation systems.…”
Section: Influence On Water Qualitymentioning
confidence: 99%